INFLUENCE OF INFORMATION ON CUSTOMS CONTROL OF PRIVATE PERSONS AND ON THE TAXATION - Valery V. Ozhigov (Статистика и экономика, 2016)
The article analyzes the state of customssupervision of the goods transported byindividuals at the airport checkpoints,basing on the example of the customsstation of Tolmachevo Airport and represents аn analysis of domestic andforeign experience of customs control ofgoods transported across the customsborder. The article reveals the problems related to the customs supervision of thegoods transported by individuals aimedat increasing the collectability of customsduties and penalties.